2018
DOI: 10.4155/fsoa-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Ultracentrifugation Versus Kit Exosome Isolation: NanoLC–MS and Other Tools Reveal Similar Performance Biomarkers, But Also Contaminations

Abstract: Aim:For isolation of exosomes, differential ultracentrifugation and an isolation kit from a major vendor were compared.Materials & methods:‘Case study’ exosomes isolated from patient-derived cells from glioblastoma multiforme and a breast cancer cell line were analyzed.Results:Transmission electron microscopy, dynamic light scattering, western blotting, and so forth, revealed comparable performance. Potential protein biomarkers for both diseases were also identified in the isolates using nanoLC–MS. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…It is demonstrated that sEVs obtained by a polymer-based commercial precipitation kit contained abundant contaminants, including aggregated proteins [24,25]. Basically, a principal of these kits is similar to the PEG method in the present study where the aqueous solubility of sEVs is reduced [15].…”
Section: Discussionmentioning
confidence: 93%
“…It is demonstrated that sEVs obtained by a polymer-based commercial precipitation kit contained abundant contaminants, including aggregated proteins [24,25]. Basically, a principal of these kits is similar to the PEG method in the present study where the aqueous solubility of sEVs is reduced [15].…”
Section: Discussionmentioning
confidence: 93%
“…Thirdly, we isolated our exosomes by ultra-centrifugation and ultra-filtration using a 100 kDa MWCO ultrafiltration filter, which could allow the possibility of other extracellular vesicles and proteins larger than 100 kDa to also be isolated alongside the exosomes. Alternatively, we could have used a commercially available exosome isolation kit, however studies have shown that exosomes isolated via kits could potentially contain contamination from chemicals in the kits that could affect in-vivo applications and analysis 50,51 . Lastly, we presented here the proteomic and genomic composition of LSC-Sec and LSC-Exo, respectively, but it would be clinically and pharmaceutically beneficial to determine which proteins, small molecules, or RNAs are the functional components capable of achieving the therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that density gradient ultracentrifugation gave the purest exosome preparations, while the other three techniques also co-isolate contaminating factors. Similarly, Skottvoll et al (2019) evaluated the performance of different isolation methods based on differential ultracentrifugation and a commercial isolation kit (total exosome isolation reagent). These results shown that the two isolation methods had similar performance with only some differences based on the origin of the cell.…”
Section: Extracellular Vesicles: Origins and Functionsmentioning
confidence: 99%